Analysis of Misinterpretations of Seven Verses in Surah Al-Baqarah: A Study from the Perspective of Quranic Exegesis - Ali Akbar; Mohd Nazri Johari; Muhammad Fawwaz; Mohd Firdaus (Yayasan Adra Karima Hubbi, 2024)
Background. The Quran, revealed to Prophet Muhammad (SAW) over 23 years in Arabic, serves as a comprehensive guide for humanity. Its preservation and reliable transmission make it central to Islamic teachings. However, understanding the Quran requires Tafsir (exegesis), which provides essential context, linguistic insights, and explanations. Despite this, many interpret Quranic verses without proper knowledge of Tafsir, resulting in widespread misinterpretations. Surah Al-Baqarah, a chapter covering diverse themes, is particularly vulnerable to such misunderstandings. Purpose. This study aims to address common misinterpretations of seven selected verses in Surah Al-Baqarah by relying on established Tafsir works. The objective is to rectify these errors, promote accurate understanding of the Quran, and emphasize the necessity of using scholarly resources to interpret its teachings. Method. The research employs a qualitative literature review method. Data is sourced from books, scholarly articles, and journals that discuss Quranic exegesis. The study examines interpretations of the chosen verses using classical Tafsir works, including those by renowned scholars, to clarify their meanings and provide contextual understanding. Results. The analysis identifies key causes of misinterpretation, including neglect of historical and textual context, linguistic misunderstandings, and cultural biases. By referring to authoritative Tafsir, the study provides accurate explanations of the seven verses, reinforcing their intended meanings. Conclusion. The study highlights the risks of misinterpreting Quranic verses and underscores the importance of Tafsir for accurate understanding. By clarifying misconceptions in Surah Al-Baqarah, this research contributes to better public comprehension of the Quran and reinforces the need for scholarly guidance in interpreting its verses.